Correction: Emerging per- and polyfluoroalkyl substances (PFAS) in human milk from Sweden and China. Issue 1 (5th January 2021) - Awad, Raed; Zhou, Yihui; Nyberg, Elisabeth; Namazkar, Shahla; Yongning, Wu; Xiao, Qianfen; Sun, Yaije; Zhu, Zhiliang; Bergman, Åke; Benskin, Jonathan P.
Abstract : Correction for 'Emerging per- and polyfluoroalkyl substances (PFAS) in human milk from Sweden and China' by Raed Awad et al., Environ. Sci.: Processes Impacts, 2020, 22, 2023–2030, DOI: ; 10.1039/D0EM00077A .